Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 32734 by caravan msup abdo. last updated on 01/Apr/18

1) a≥0  calculate ∫_0 ^a  ((n^2  −x^2 )/((n^2  +x^2 )^2 ))dx with  n integr  2) find  ∫_0 ^∞   ((n^2  −x^2 )/((n^2  +x^2 )^2 ))dx  3)calculate  Σ_(n=1) ^∞   ∫_0 ^∞  ((n^2  −x^2 )/((n^2  +x^2 )^2 )) dx .

1)a0calculate0an2x2(n2+x2)2dxwithnintegr2)find0n2x2(n2+x2)2dx3)calculaten=10n2x2(n2+x2)2dx.

Commented by abdo imad last updated on 08/Apr/18

let put I_n (a) = ∫_0 ^a   ((n^2  −x^2 )/((n^2  +x^2 )))dx   I_n (a) =n^2  ∫_0 ^a    (dx/((n^2  +x^2 )^2 ))  − ∫_0 ^a  ((n^2  +x^2  −n^2 )/((n^2  +x^2 )))dx  =2n^2  ∫_0 ^a    (dx/((n^2  +x^2 )^2 )) −∫_0 ^a   (dx/(n^2  +x^2 ))  .ch.x=nt give  ∫_0 ^a    (dx/(n^2  +x^2 )) = ∫_0 ^(a/n)     ((ndt)/(n^2 (1+t^2 ))) =(1/n) arctan((a/n)) also  ∫_0 ^a     (dx/((n^2  +x^2 )^2 )) = ∫_0 ^(a/n)    ((ndt)/(n^4 ( 1+t^2 )^2 )) = (1/n^3 ) ∫_0 ^(a/n)    (dt/((1+t^2 )^2 ))  =_(t=tanθ)    (1/n^3 ) ∫_0 ^(arctan((a/n)))       (((1+tan^2 θ)dθ)/((1+tan^2 θ)^2 ))  = (1/n^3 ) ∫_0 ^(arctan((a/n)))    (dθ/(1+tan^2 θ)) =(1/n^3 ) ∫_0 ^(arctan((a/n)))  (cos^2 θ)dθ  =(1/(2n^3 )) ∫_0 ^(arctan((a/n)))  (1+cos(2θ))dθ  = ((arctan((a/n)))/(2n^3 ))   + (1/(4n^3 )) [sin(2θ)]_0 ^(arctan((a/n)))   = ((arctan((a/n)))/(2n^3 )) +(1/(4n^3 )) sin(2arctan((a/n)))⇒  I_n (a) = ((arctan((a/n)))/n)  + (1/(2n)) sin(2arctan((a/n))) −(1/n) arctan((a/n))  I_n (a)  = (1/(2n)) sin (2 arctan((a/n))) .

letputIn(a)=0an2x2(n2+x2)dxIn(a)=n20adx(n2+x2)20an2+x2n2(n2+x2)dx=2n20adx(n2+x2)20adxn2+x2.ch.x=ntgive0adxn2+x2=0anndtn2(1+t2)=1narctan(an)also0adx(n2+x2)2=0anndtn4(1+t2)2=1n30andt(1+t2)2=t=tanθ1n30arctan(an)(1+tan2θ)dθ(1+tan2θ)2=1n30arctan(an)dθ1+tan2θ=1n30arctan(an)(cos2θ)dθ=12n30arctan(an)(1+cos(2θ))dθ=arctan(an)2n3+14n3[sin(2θ)]0arctan(an)=arctan(an)2n3+14n3sin(2arctan(an))In(a)=arctan(an)n+12nsin(2arctan(an))1narctan(an)In(a)=12nsin(2arctan(an)).

Commented by abdo imad last updated on 08/Apr/18

we have  sin(2arctan((a/n)))=2sin(arctan((a/n)))cos(arctsn((a/n)))  but we have the frmulae sin(arctanx)= (x/(√(1+x^2 )))  cos(arctanx) = (1/(√(1+x^2 ))) ⇒  I_n (a) =(1/n)  ((a/n)/(√(1+(a^2 /n^2 ))))  (1/(√(1+(a^2 /n^2 )))) = (a/((1+(a^2 /n^2 ))))= ((an^2 )/(n^2  +a^2 ))

wehavesin(2arctan(an))=2sin(arctan(an))cos(arctsn(an))butwehavethefrmulaesin(arctanx)=x1+x2cos(arctanx)=11+x2In(a)=1nan1+a2n211+a2n2=a(1+a2n2)=an2n2+a2

Commented by abdo imad last updated on 08/Apr/18

2) ∫_0 ^∞  ((n^2  −x^2 )/((n^2  +x^2 )^2 )) =lim_(a→+∞)  I_n (a) =lim_(a→+∞)   ((an^2 )/(n^2  +a^2 ))  =lim_(a→+∞)   (n^2 /a) =0 .

2)0n2x2(n2+x2)2=lima+In(a)=lima+an2n2+a2=lima+n2a=0.

Answered by hknkrc46 last updated on 04/Apr/18

1)x=ntanu⇒dx=n(1+tan^2 u)du=nsec^2 udu  x→a,u→arctan((a/n)) ∧ x→0,u→0  ∫_0 ^a ((n^2 −x^2 )/((n^2 +x^2 )^2 ))dx=∫_0 ^(arctan((a/n))) ((n^2 −(ntanu)^2 )/((n^2 +(ntanu)^2 )^2 ))nsec^2 udu  =∫_0 ^(arctan((a/n))) ((n^2 −n^2 tan^2 u)/((n^2 +n^2 tan^2 u)^2 ))nsec^2 udu  =∫_0 ^(arctan((a/n))) ((n^2 (1−tan^2 u))/((n^2 (1+tan^2 u))^2 ))nsec^2 udu  =∫_0 ^(arctan((a/n))) (((n^2 cos2u)/(cos^2 u))/(n^4 sec^4 u))nsec^2 udu  =∫_0 ^(arctan((a/n))) ((cos2u)/n)du=((sin2u)/(2n))∣_0 ^(arctan((a/n))) =((sin(2arctan((a/n))))/(2n))  =((sin(arctan((a/n)))cos(arctan((a/n))))/n)=(a/(a^2 +n^2 ))  ★ arctan((a/n))=ψ⇒tanψ=(a/n)⇒sinψ=(a/(√(a^2 +n^2 ))) ∧ cosψ=(n/(√(a^2 +n^2 )))  2)∫_0 ^∞ ((n^2 −x^2 )/((n^2 +x^2 )^2 ))dx=lim_(a→∞) ∫_0 ^a ((n^2 −x^2 )/((n^2 +x^2 )^2 ))dx=lim_(a→∞) (a/(a^2 +n^2 ))=0  3)Σ_(n=1) ^∞ ∫_0 ^∞ ((n^2 −x^2 )/((n^2 +x^2 )^2 ))dx=lim_(k→∞) Σ_(n=1) ^k ∫_0 ^∞ ((n^2 −x^2 )/((n^2 +x^2 )^2 ))dx=0

1)x=ntanudx=n(1+tan2u)du=nsec2uduxa,uarctan(an)x0,u00an2x2(n2+x2)2dx=0arctan(an)n2(ntanu)2(n2+(ntanu)2)2nsec2udu=0arctan(an)n2n2tan2u(n2+n2tan2u)2nsec2udu=0arctan(an)n2(1tan2u)(n2(1+tan2u))2nsec2udu=0arctan(an)n2cos2ucos2un4sec4unsec2udu=0arctan(an)cos2undu=sin2u2n0arctan(an)=sin(2arctan(an))2n=sin(arctan(an))cos(arctan(an))n=aa2+n2arctan(an)=ψtanψ=ansinψ=aa2+n2cosψ=na2+n22)0n2x2(n2+x2)2dx=lima0an2x2(n2+x2)2dx=limaaa2+n2=03)n=10n2x2(n2+x2)2dx=limkn=1k0n2x2(n2+x2)2dx=0

Terms of Service

Privacy Policy

Contact: info@tinkutara.com